The Effect Of Problem Solving Methods On Students' Learning Outcomes - Sindi Kartini, Syahraini Ritonga, Basyarul Ulya (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to determine the effect of the Problem Solving method on the learning outcomes of students at SMP Negeri 1 Bilah Barat. The Problem Solving method is a learning approach that emphasizes critical thinking skills and problem solving in the learning process. This study uses an experimental method with a pretest-posttest control group design. The research sample consisted of two groups, namely the experimental class, namely VII D which uses the Problem Solving method and the control class, namely VII B which uses the conventional method. Data collection was carried out through a test in the form of a total of 30 questions on learning outcomes and observations during the learning process. Data analysis used a t-test statistical test to determine the differences in learning outcomes between the two groups. The results showed that there was a significant difference between the learning outcomes of students taught using the Problem Solving method compared to the conventional method. Students in the experimental class showed an increase in conceptual understanding and better critical thinking skills. Thus, the Problem Solving method has proven effective in improving the learning outcomes of students at SMP Negeri 1 Bilah Bara